Induction of Dendritic Cell Maturation and Activation by a Potential Adjuvant, 2-Hydroxypropyl-β-Cyclodextrin - Kim, Sun Kyung; Yun, Cheol-Heui; Han, Seung Hyun (Frontiers in Immunology, 2016)
2-Hydroxypropyl-β-cyclodextrin (HP-β-CD) is a chemically modified cyclic oligosaccharide produced from starch that is commonly used as an excipient. Although HP-β-CD has been suggested as a potential adjuvant for vaccines, its immunological properties and mechanism of action have yet to be characterized. In the present study, we investigated the maturation and activation of human dendritic cells (DCs) treated with HP-β-CD. We found that DCs stimulated with HP-β-CD exhibited a remarkable upregulation of costimulatory molecules, MHC proteins, and PD-L1/L2. In addition, the production of cytokines such as TNF-α, IL-6, and IL-10 was modestly increased in DCs when treated with HP-β-CD. Furthermore, HP-β-CD-sensitized DCs markedly induced the proliferation and activation of autologous T lymphocytes. HP-β-CD also induced a lipid raft formation in DCs. In contrast, filipin, a lipid raft inhibitor, attenuated HP-β-CD-induced DC maturation, the cytokine expression, and the T lymphocyte-stimulating activities. To determine the in vivo relevance of the results, we investigated the adjuvanticity of HP-β-CD and the modulation of DCs in a mouse footpad immunization model. When mice were immunized with ovalbumin in the presence of HP-β-CD through a hind footpad, serum ovalbumin-specific antibodies were markedly elevated. Concomitantly, DC populations expressing CD11c and MHC class II were increased in the draining lymph nodes and the expression of costimulatory molecules was upregulated. Collectively, our data suggest that HP-β-CD induces phenotypic and functional maturation of DCs mainly mediated through lipid raft formation, which might mediate the adjuvanticity of HP-β-CD.